2015
DOI: 10.1159/000370192
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Index in Preterm Infants during the First 3 Days of Life: Reference Values and Relation with Clinical Variables

Abstract: Background: The perfusion index (PI) derived from pulse oximetry readings represents the ratio of pulsatile (arterial blood) and nonpulsatile contributors to infrared light absorption. PI has been shown to correlate with cardiac performance. In theory, PI is readily available on every pulse oximeter; therefore, no additional sensors or infant handling are required. Currently, reference values are lacking in (preterm) neonates and the association with common clinical conditions is unclear. Objectives: To establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…We believe that with PDA there is a decrease in the DC component of the postductal PI due to the overall lower perfusion and decreased mean arterial pressure at the postductal sites (30,31). Furthermore, our findings are consistent with the report by Alderliesten et al (9) who found in a study of 342 neonates that infants with hsPDA had higher postductal PI than infants without hsPDA. They attributed this finding to a hyperdynamic circulation with a widened pulse-pressure resulting in an increase in the AC component.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We believe that with PDA there is a decrease in the DC component of the postductal PI due to the overall lower perfusion and decreased mean arterial pressure at the postductal sites (30,31). Furthermore, our findings are consistent with the report by Alderliesten et al (9) who found in a study of 342 neonates that infants with hsPDA had higher postductal PI than infants without hsPDA. They attributed this finding to a hyperdynamic circulation with a widened pulse-pressure resulting in an increase in the AC component.…”
Section: Discussionsupporting
confidence: 94%
“…We expected to observe a steady preductal PI and a decreased postductal PI leading to a larger ΔPI in infants with PDA. The negative ΔPI (Figure 3) is likely a combination of a decreased preductal PI (reported by Karadag et al (25)) and a postductal PI that is either steady (reported by Vidal et al (12)) or increased (reported by Alderliesten et al (9)). These results have a combined effect towards a negative ΔPI value found in infants with PDA.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We also determined that this measurement was highly reproducible and that the measurements obtained in the right upper limb were consistently higher than either lower limb, which might reflect transitional circulatory changes. Reference values for continuous PI measurements during the first 3 days of life have been recently published 56. Rather than looking at absolute values, we recently evaluated the temporal evolution of different aspects of the PI signal in a cohort of ELGANs over the first 24 hours of life 57.…”
Section: Pulsatility Index (Pi)mentioning
confidence: 99%